Multifactor Evaluation Process for a Decision Support System for Selecting the Best Students - Ryando, M. Bucci; Ferawati, Ferawati; Iqbal, Muchamad; Setiawan, Prayoga (Institut Teknologi dan Bisnis Bina Sarana Global, 2024)
The utilization of information systems can significantly contribute to enhancing efficiency and service delivery at MA Daarul Falah, an educational institution in Pondok Pesantren Daarul Falah. Previously, there were often issues with subjective assessment of high-achieving students and inadequate archiving of previous years' assessment records. This study aims to expedite the collection of student assessment data from each class, automate the student grading process, and improve the objectivity of the school's assessments of all students. The method employed in this research is the Multi-Factor Evaluation Process (MFEP), implemented using the PHP programming language. The results of the study indicate that students who receive a total evaluation score above 90.00 are considered eligible to serve at Pondok Pesantren Daarul Falah, while those who score below 90.00 are deemed ineligible to serve there.